Reproductive and persistence strategy of the liverwort Arnellia fennica after the last glaciation in the area of disjunction in Central Europe (Polish Tatra Mountains, carpathians) - Piotr Górski; Monika Szczecińska; Jakub Sawicki (Scientific Reports)
Abstract The liverwort Arnellia fennica has a circumarctic distribution with disjunct and scarce localities in the Alps, Carpathians, and Pyrenees. Within the Carpathians, it is only known from the Tatra Mountains (in Poland), where so far only four occurrences have been documented in the forest belt of the limestone part of the Western Tatras. The species is considered a tertiary relict, which owes its survival during the last glaciation period to low-lying locations in areas not covered by ice. Previously, it has been demonstrated that this plant does not produce gemmae in the Tatra Mountains, nor does it reproduce sexually, hence it has not spread in this massif despite the high availability of potential habitats. These studies address the following questions: (1) why A. fennica, an arctic-alpine species, has only been found at low elevations in the Tatra Mountains so far, (2) what were the possibilities of its survival during the glaciation period as verified based on the latest paleoglaciological map, (3) how this species persists in the Tatras and why it remains a rare plant. As a result, nine additional new occurrences were found, bringing the total to 13 throughout the massif. Some of the sites were found in the high mountain area. For the first time, the production of gemmae in the Tatra population of A. fennica was observed and documented, along with the presence of male specimens of this dioecious species. Genetic studies have shown that individuals from all three groups of sites are genetically homogeneous, indicating a lack of sexual reproduction. The only way of dispersal for A. fennica in the Tatras is through propagule production. The uniqueness and specificity of these structures have been described, which differ significantly from the common model known in liverworts. The rarity of the species in the Tatra massif is attributed to the inefficient mode of vegetative reproduction and the absence of sexual reproduction. Paleoglaciological analysis of all montane sites (historical and new) of A. fennica showed that half were located in areas covered by glaciers. The hypothesis of this liverwort’s survival during the glaciation period, at lower elevations, should be rejected. In light of the new data obtained, montane localities should be considered as secondary, which could have arisen after the glacier retreated only from high-mountain populations producing propagules transported downhill.